Model Pembelajaran Jigsaw Untuk Meningkatkan Motivasi Belajar Pada Materi Analisis Potensiometri - Esti Triningsih (Universitas Mathla'ul Anwar Banten, 2022)
This research is a classroom action research that aims to determine the extent to which the application of the Jigsaw cooperative learning model can increase students' learning motivation. The subjects of this study were students of class XI APL 2 SMKN 1 Cangkringan semester 2 for the academic year 2021/2022, totaling 35 people consisting of 13 boys and 22 girls. . The research took place in 2 cycles consisting of 4 stages, namely planning, implementation and observation, and reflection. Student motivation data was collected using a questionnaire. The collected data were analyzed descriptively and qualitatively. The results showed that the use of the Jigsaw learning model could increase the learning motivation of students in class XI APL 2 SMKN 1 Cangkringan in the subject of chemical analysis of potentiometric analysis instruments. This can be proven by an increase in the percentage of students' motivation and learning outcomes in each cycle. In the first cycle the percentage of students' learning motivation was 62.93%, then in the second cycle it reached 72.65%.